A Mason-Pfizer Monkey virus Gag-GFP fusion vector allows visualization of capsid transport in live cells and demonstrates a role for microtubules - Clark, Jasmine; Grznarova, Petra; Stansell, Elizabeth; Diehl, William; Lipov, Jan; Spearman, Paul; Ruml, Tomas; Hunter, Eric (PloS one, 2013)
Immature capsids of the Betaretrovirus, Mason-Pfizer Monkey virus (M-PMV), are assembled in the pericentriolar region of the cell, and are then transported to the plasma membrane for budding. Although several studies, utilizing mutagenesis, biochemistry, and immunofluorescence, have defined the role of some viral and host cells factors involved in these processes, they have the disadvantage of population analysis, rather than analyzing individual capsid movement in real time. In this study, we created an M-PMV vector in which the enhanced green fluorescent protein, eGFP, was fused to the carboxyl-terminus of the M-PMV Gag polyprotein, to create a Gag-GFP fusion that could be visualized in live cells. In order to express this fusion protein in the context of an M-PMV proviral backbone, it was necessary to codon-optimize gag, optimize the Kozak sequence preceding the initiating methionine, and mutate an internal methionine codon to one for alanine (M100A) to prevent internal initiation of translation. Co-expression of this pSARM-Gag-GFP-M100A vector with a WT M-PMV provirus resulted in efficient assembly and release of capsids. Results from fixed-cell immunofluorescence and pulse-chase analyses of wild type and mutant Gag-GFP constructs demonstrated comparable intracellular localization and release of capsids to untagged counterparts. Real-time, live-cell visualization and analysis of the GFP-tagged capsids provided strong evidence for a role for microtubules in the intracellular transport of M-PMV capsids. Thus, this M-PMV Gag-GFP vector is a useful tool for identifying novel virus-cell interactions involved in intracellular M-PMV capsid transport in a dynamic, real-time system.
Keywords: Molecular Imaging; biologický transport; Green Fluorescent Proteins; Movement; Fluorescent Dyes; Kinetics; Gene Products, gag; mikrotubuly; Proviruses; pohyb; Capsid; HEK293 Cells; Recombinant Fusion Proteins; kapsida; rekombinantní fúzní proteiny; lidé; Protein Transport; genové produkty gag; molekulární zobrazování; proviry; fluorescenční barviva; HEK293 buňky; zelené fluorescenční proteiny; transport proteinů; Biological Transport; Virus Assembly; genetické vektory; sestavení viru; Mason-Pfizer monkey virus; Masonův-Pfizerův opičí virus; Microtubules; Cell Survival; viabilita buněk; buněčná membrána; Genetic Vectors; kinetika; Cell Membrane; Humans